Bioetnomelayu Course: A Reflection - Alaniyah Syafaren; Rian Vebrianto; Mery Berliyan (Sosial Budaya, 2018)
The University of Riau holds a course known as "Bioetnomelayu." This course discusses the local wisdom of Malay culture in the bioenvironmental context This study was aimed to gain more extensive understanding concerning the implementation of bioethnomelayu in the classroom, assessed from the students' experience This is a qualitative research with in-depth interview method as a survey design The study shows that the bioethnomelayu course integrates biological sciences and indigenous entities, cultures and local wisdom in environmental management; thus, providing an outstanding experience in understanding local wisdom with the scientific basis for preserving the environment, even though about bioethnomelayu course has challenge like the literature regarding the local wisdom is limited. But it is very important to recognize the local wisdom of their ancestral heritage, to inherit the knowledge to the future generations. The implications for society can understand the local natural resources and how to develop them sustainably and environmentally friendly because Riau Province has diverse ecosystems and natural resources which are closely related to the nature in their daily life. This is represented in the local phrase of "nature as a teacher.